Preconceito contra diversidade sexual e de gênero e prática clínica em psicologia - Gaspodini, Icaro Bonamigo (Universidade do Vale do Rio dos Sinos, 2017)
The objective of this research was to investigate how psychologists’ beliefs and attitudes and the psychological knowledge are related to prejudice against sexual and gender diversity. The dissertation is composed of three studies. In Study I, a systematic literature review (2006-2016) showed that most Brazilian psychological studies on prejudice neglect sexual orientations different from homosexuality, as well as non-cisgender identities or expressions. In Study II, we investigated prejudice against sexual and gender diversity in 497 Brazilian psychologists from 22 out of 23 Regional Psychology Counsels. Participants showed low levels of prejudice, but we consider them worrisome because it was an extreme measure. When investigated in relation to personal beliefs about the nature of diversity, prejudice showed to be more associated with psychological explanations, such as perversion or unsatisfactory conflict resolution with parental figures. In Study III, we explored how sexual and diversity issues are experienced by 14 female psychologists from five cities in the southernmost state in Brazil (Rio Grande do Sul). We found perceptions of not being prepared, presence of pathologizing knowledge in graduation, prejudicial beliefs and attitudes, use of inadequate language, and pathologizing clinical practices. This dissertation shows that, if psychologists conduct their clinical practice based on what they learned through graduation, together with their personal beliefs and attitudes, then the combination of pathologizing knowledge and prejudicial beliefs and attitudes may probably result in predicament to the health of the LGBT public. Although the manifestation of prejudice had been minored in all studies due to sample and study design characteristics, we find troublesome to have found prejudice in every psychological aspect we investigated: in literature, in education, in clinical practice, and in psychologists themselves.
Keywords: Preconceito; Homofobia; Formação do psicólogo; Atuação do psicólogo; Atitudes do terapeuta; Psicologia clínica; Prejudice; Homophobia; Psychologist education; Psychologist performance; Therapist attitudes; Clinical psychology; ACCNPQ::Ciências Humanas::Psicologia